2004
DOI: 10.1152/ajplung.00420.2002
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of KL-6, a lung epithelial cell marker, in plasma and epithelial lining fluid in acute respiratory distress syndrome

Abstract: Elevation of KL-6, a lung epithelial cell marker, in plasma and epithelial lining fluid in acute respiratory distress syndrome. Am J Physiol Lung Cell Mol Physiol 286: L1088 -L1094, 2004. First published September 5, 2003 10.1152 10. /ajplung. 00420.2002 is a pulmonary epithelial mucin more prominently expressed on the surface membrane of alveolar type II cells when these cells are proliferating, stimulated, and/or injured. We hypothesized that high levels of KL-6 in epithelial lining fluid and plasma would r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
152
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(166 citation statements)
references
References 30 publications
13
152
1
Order By: Relevance
“…It was assumed before starting this study that serum levels of KL-6 and SP-D in AE-IPF would be higher than those in S-IPF patients because previous reports have suggested that KL-6 and SP-D might be useful markers for interstitial pneumonias (Ohnishi et al 2002;Takahashi et al 2000). However, Ishizaka et al reported that at the onset of acute lung injury, plasma levels of KL-6 were similar to those of controls, perhaps because of its relatively large molecular size (Ishizaka et al 2004). In addition, in the current study, serum levels of KL-6 and SP-D levels were elevated even in patients with S-IPF (when compared with normal ranges), consistent with previous reports (Ohnishi et al 2002;Takahashi et al 2000).…”
Section: Discussionmentioning
confidence: 92%
“…It was assumed before starting this study that serum levels of KL-6 and SP-D in AE-IPF would be higher than those in S-IPF patients because previous reports have suggested that KL-6 and SP-D might be useful markers for interstitial pneumonias (Ohnishi et al 2002;Takahashi et al 2000). However, Ishizaka et al reported that at the onset of acute lung injury, plasma levels of KL-6 were similar to those of controls, perhaps because of its relatively large molecular size (Ishizaka et al 2004). In addition, in the current study, serum levels of KL-6 and SP-D levels were elevated even in patients with S-IPF (when compared with normal ranges), consistent with previous reports (Ohnishi et al 2002;Takahashi et al 2000).…”
Section: Discussionmentioning
confidence: 92%
“…This is in contrast to bronchoalveolar lavage (BAL), which samples two sites of infection, i.e., fluid lining the small airways distal to the point of the wedge of the tip of the bronchoscope (alveolar ELF) and alveolar macrophage (AM). BMS is useful for measuring the concentrations of biochemical substances, such as KL-6, albumin, and tumor markers, in bronchial ELF [4,5]. We have also used this technique to obtain bronchial ELF on the airway surface and determine the time versus concentration profile of levofloxacin, a model antibiotic [6].…”
Section: Bronchoscopic Microsampling (Bms) Is a New Technique For Repmentioning
confidence: 99%
“…However, plasma KL-6 levels are not elevated in noninterstitial lung diseases such as bacterial pneumonia, bronchial asthma, and pulmonary emphysema (9). Similar pathological changes seen in interstitial pneumonia in the lung are also predominant in BPD (7,12,13). Plasma KL-6 can be a clinically useful early marker for BPD.…”
Section: Introductionmentioning
confidence: 70%